Shear strength of stiffened steel shear walls with considering the gravity load effect through a three-segment distribution. (February 2021) - Li, Jie; Lv, Jia-Qi; Sivakumar, Vinu; Chen, Yu; Huang, Xin; Lv, Yang; Chouw, Nawawi
Abstract: Former investigations have shown that the gravity load will significantly reduce the shear strength of the steel shear walls (SSW), especially in the case of a stocky wall that has high buckling stress under heavy compression load. However, only a few have been carried out on stiffened SSW, even though it has high compression buckling stress. The present study aims to narrow the knowledge gap by conducting a theoretical analysis and a numerical evaluation. The stiffened SSW is divided into several sub-walls by vertical and horizontal stiffeners. For each sub-wall, a three-segment vertical stress distribution under the gravity load is proposed. The tension field stress of inclination tension strips of each sub-wall, with considering the effect of the gravity load through the proposed three-segment vertical stress distribution, is determined through the Von Mises yield criterion. Shear strength of the wall is calculated as the sum of the shear strength of each sub-wall, while that of the boundary frame is determined according to a wall-frame model. To evaluate the proposed approach, an experimentally verified finite element model using the software ANSYS/LS-DYNA is developed. The results show that the proposed approach is able to accurately consider the gravity load effect of the stiffened SSWs of different stiffeners configurations.